Effect of feeding a protein supplement during the latter part of the grazing season to two-year-old steers on bluestem pasture. - Baker, F.H.; Smith, E.F.; Cox, R.F.; Good, D.L. (Kansas Agricultural Experiment Station, 2012)
Twenty head of good quality two-year-old Hereford steers were used. They were wintered and summered on bluestem pasture until August 4, when this test was initiated. The steers were divided into two uniform lots and grazed on bluestem pasture with the following treatment from August 4, 1954, to October 15, 1954: Lot 1-No supplement. Lot 2-2 pounds of cottonseed cake per head daily.
Keywords: Beef; Protein; Gains; Cottonseed